Symposium on the Report of the Commission on Emigration and other population problems - Carter, C. F.; Duncan, G. A.; Nevin, Donal; O Buachalla, Liam (Statistical and Social Inquiry Society of Ireland, 1956)
My comments are limited to two points, one demographic and one economic. In matters demographic Ireland is obviously out of step with the rest of the world, and it is difficult to avoid the sense of guilt which comes from being out of step with one's fellows. Yet if one looks ahead towards the end of the century, the future is overshadowed by the disastrous rate of multiplication of mankind. The Society has reason to be proud of the fact that, small and poor as this country is, it has one of the finest statistical services in the world.
Report of the Commission on Emigration
Read before the Society, 27 January 1956
Keywords: Irish population; Irish emigration; Demographics; 314.15